The effect of surface mechanical attrition treatment on texture evolution and mechanical properties of AZ31 magnesium alloy - Peng, Jinhua (2020)
AZ31 hot-rolled plates with gradient nano-grained surface were produced by surface mechanical attrition treatment (SMAT). The grain size was refined to nanoscale at the surface layer via twinning and dynamic recrystallization (DRX). The micro-hardness at the top layer had a 132% improvement and the strengthening trend could be divided into three stages. The (0002) basal texture of the base material was weakened during SMAT, indicated by the inclination of (0002) poles, the decrease of maximum pole density and the divergence of contour lines. The inclined impacting direction of steel balls, the spherical shape of the balls and the activation of non-basal slip at the top surface were responsible for the variation. The yield strength was enhanced after SMAT and the increment during tensile test was higher than that during compression due to the different deformation mechanism. Texture weakening had little effect on mechanical properties due to the nano-grains and strong strain hardening at the top surface layer.